2010
DOI: 10.1016/j.jdent.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidins increase collagen biodegradation resistance in the dentin/adhesive interface when included in an adhesive

Abstract: Objectives-Contemporary methods of dentin bonding could create hybrid layers (HLs) containing voids and exposed, demineralized collagen fibers. Proanthocyanidins (PA) have been shown to crosslink and strengthen demineralized dentin collagen, but their effects on collagen degradation within the HL have not been widely studied. The purpose of this study was to compare the morphological differences of HLs created by BisGMA/HEMA model adhesives with and without the addition of grape seed extract PA under condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 31 publications
1
84
1
4
Order By: Relevance
“…As mentioned in PA-collagen interactions, hydrogel formed by GAGs can function as a molecular-sieve which limits resin penetration between collagen fibrils, so such diminishing effect on GAGs content will raise hybrid layer quality. HYP assay confirmed the reinforcing mechanism of GSE and GD on collagen fibrils, however there was an inverse relationship between GSE concentration and HYP release into the incubation media, while the same relationship was not found for GD group, probably due to the restricted covalent interactions of GD with dentin 85,93,94) , it was found that transient PA pretreatment of demineralized dentin before adhesive bonding will not compromise the D.C and curing behavior of the adhesive. Current study showed that in a same pre-treatment time, 15% PA group bonded with Adper TM Single Bond 2 (SB, 3M ESPE) showed higher µTBS values compared to GD-pretreated group.…”
Section: Transient Collagen Cross-linking By Pa-containing Preconditimentioning
confidence: 77%
See 1 more Smart Citation
“…As mentioned in PA-collagen interactions, hydrogel formed by GAGs can function as a molecular-sieve which limits resin penetration between collagen fibrils, so such diminishing effect on GAGs content will raise hybrid layer quality. HYP assay confirmed the reinforcing mechanism of GSE and GD on collagen fibrils, however there was an inverse relationship between GSE concentration and HYP release into the incubation media, while the same relationship was not found for GD group, probably due to the restricted covalent interactions of GD with dentin 85,93,94) , it was found that transient PA pretreatment of demineralized dentin before adhesive bonding will not compromise the D.C and curing behavior of the adhesive. Current study showed that in a same pre-treatment time, 15% PA group bonded with Adper TM Single Bond 2 (SB, 3M ESPE) showed higher µTBS values compared to GD-pretreated group.…”
Section: Transient Collagen Cross-linking By Pa-containing Preconditimentioning
confidence: 77%
“…For the first time in 2010, Green et al 85) , added 5 wt% GSE PA into a model adhesive similar to single bond plus adhesive (3M ESPE, St. Paul, MN, USA) 86) , so that final PA-incorporated model adhesive was composed of solvent(ethanol)/monomer/PA mass ratio of 37/60/3. It was reported that despite the dark color of PA, there was no considerable color difference between PA-incorporated model adhesive and pure adhesive.…”
Section: Pa-incorporated Dental Adhesivesmentioning
confidence: 99%
“…Proanthocyanidin consists of a free hydroxyl phenyl group that has the ability to bind a protein amino acid. The phenyl hydroxyl group forms [10,[17][18][19]. Therefore, in this study, the application of GSE solution for 30 seconds was sufficient for increasing the cross-linking of collagen dentin, according to research by Liu and Wang [9].…”
Section: Discussionmentioning
confidence: 89%
“…It appears that increasing the collagen resistance to biodegradation can further stabilize the resin-dentin interface (8)(9)(10). Collagen cross-linkers can protect collagen fibrils from degradation and enhance their mechanical and chemical properties (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%